Criminalistic Registration: Features and Prospects for Developing Kazakh and Foreign Practices - SADYRBEKOVA, Gulnur Khasenovna (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
This article examines the features of criminalistic registration in the Republic of Kazakhstan. Criminalistic activities play a significant role in fighting against crime and aim to uncover and investigate offences, to create the evidence base which is necessary for exposing and convicting criminals. Criminalistic registration is an integral part of these activities and their informational component, the use of which is fundamental for successful crime investigation in modern conditions. The article aims to analyze the current state of criminalistic registration in the Republic of Kazakhstan, to study foreign experience and present prospects for the formation and use of criminalistic registration data. The author of the article searches historical background of the modern criminalistic registration system, its organization and legal framework in the Republic of Kazakhstan, the global experience of combining and using different information databases to investigate crimes, assess the possibilities of advanced information technologies and international information bases to fight against crimes. As a result, the author has evaluated the criminalistic registration in Kazakhstan, its organizational and legal foundations, and prospects for its further development. The article suggests creating unified information system at the global level which will provide more opportunities for the use of forensic information. The novelty of the article lies in the fact that it proposes ways of international information interaction in order to fight against crime based on a deep analysis of the global use of forensic information bases.